PENGARUH KESADARAN MEREK, PERSEPSI KUALITAS DAN ASOSIASI MEREK TERHADAP LOYALITAS MEREK MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA PENGGUNA IM3 (STUDI PADA MAHASISWA S1 UNIVERSITAS DIPONEGORO SEMARANG) - Diah Tri Utami; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2017)
This research is motivated by the development of the world of technology,especially mobile phones that result in intense competition among companies. IM3 alwaysstrive to provide the best service to consumers through the services they have. So IM3managed to become the top brand for the category of Top of Mind simcard in 2014 to 2016.In addition, the total IM3 users in each year also increased.The aims of research is to determine the effect of brand awareness, perceivedquality, and brand association towards the brand loyalty of IM3 user, in partially orsimultaneously through customer satisfaction as an intervening variable. The population ofthis research is all undergaduate students in Diponegoro University who use IM3. Samplingis done gradually with Multistage Sampling method. Samples obtained on this research were96 respondents. The data for this research were obtained from questionnaires, literaturestudies, and interview to respondents. Analytical methods used validity test, reliability test,simple linear regression analysis and multiple linear regression analysis, coefficient ofdetermination, significance test (t test) and (f test) and path analysis with SPSS tool.The results of this research showed that the variable of brand awareness (X1),perceived quality (X2), brand association (X3), and customer satisfaction (Z) have a strongeffect on brand loyalty (Y). It can be seen from the coefficient of multiple correlation that isequal to 0,769, and F table test equal to 33,023 bigger than F table. The result of pathanalysis concerning on the influence variable of brand awareness (X1), perceived quality(X2), and brand association (X3) toward the brand loyalty (Y) of IM3 users through customersatisfaction (Z) as intervening variable is evident. The effect of brand awareness (X1),perceived quality (X2), brand association (X3) toward brand loyalty (Y) of IM3 users will behigher if through customer satisfaction (Z).Based on the results of the research, the researcher suggested that the company willimprove the provision of information about the brand, ranging from service, productdiversity, and quality improvement in order to create IM3 user brand loyalty, making IM3 anincreasingly superior brand.